Chemical characterization of filterable PM2.5 emissions generated from regulated stationary sources in the Metropolitan Area of Costa Rica - Herrera-Murillo, Jorge (2017)
Filterable PM2.5 concentrations and their chemical characterizations were analyzed for 67 boilers and 25 indirect furnaces located in the Metropolitan Area of Costa Rica from February 2014 to November 2015. The PM2.5 samples were characterized by their composition, focusing on trace elements, inorganic ions and organic and elemental carbon. The results of PM2.5 concentrations ranged from 72 to 735 mgm-3, with the highest concentrations found for sources using biomass fuel, particularly Type B boilers, and the lowest values for diesel boilers. Further speciation of fine particulate matter (PM) showed significant levels of vanadium and nickel for boilers that use heavy fuel oil (bunker); 4886 and 1942 μgm-3, respectively. Copper and manganese were the most relevant metals for biomass burning sources, due to plant absorption from the soil. As for ion concentration, sulfate presented the highest concentrations for biomass boilers and furnaces, whereas chloride only presented the highest concentrations for furnaces. To complete the balance, organic and elemental carbon (OC and EC) analyses were made, in which biomass burning sources presented values five times higher than oil fuels. A Spearman's correlation analysis was made for the data set, revealing significant relationships between heavy metals, sulfate, and fine PM with respect to heavy fuel oil. For the biomass sources, the correlations pointed to K, Na, Mn and, in some cases, oxygen.